2016
DOI: 10.1186/s13673-016-0065-2
|View full text |Cite
|
Sign up to set email alerts
|

Baiting the hook: factors impacting susceptibility to phishing attacks

Abstract: Over the last decade, substantial progress has been made in understanding and mitigating phishing attacks. Nonetheless, the percentage of successful attacks is still on the rise. In this article, we critically investigate why that is the case, and seek to contribute to the field by highlighting key factors that influence individuals’ susceptibility to phishing attacks. For our investigation, we conducted a web-based study with 382 participants which focused specifically on identifying factors that help or hind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
77
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 29 publications
2
77
6
Order By: Relevance
“…4 that education has the highest rank among other considered factors. This result conflicts with a previous study which argued that the level of education is not significantly related to phishing victimisation [12]. But most importantly, when comparing university students with people from outside higher education institutions [44], both behave in a similar way in social networks.…”
Section: Findings and Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…4 that education has the highest rank among other considered factors. This result conflicts with a previous study which argued that the level of education is not significantly related to phishing victimisation [12]. But most importantly, when comparing university students with people from outside higher education institutions [44], both behave in a similar way in social networks.…”
Section: Findings and Discussioncontrasting
confidence: 56%
“…However, the statistic mean for this item is higher than the population mean (μ0 = 3) and has been ranked as moderately important in the scale which makes this item hard to exclude from the framework. Surprisingly, the experts did not consider gender as a very important determinant, a result that opposes many previous studies [12,23,31]. One of which was Algarni et al [31] experimental study that revealed a strong correlation between gender and response to social engineering attacks in social network contexts.…”
Section: Findings and Discussioncontrasting
confidence: 51%
See 3 more Smart Citations